2018
DOI: 10.1080/21870764.2018.1439784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb substitution on structural, electrical and electrochemical properties of LiTi2(PO4)3 as electrolyte materials for lithium ion batteries

Abstract: The NASICON (Na Super Ionic CONductors)-type materials are good ionic conductors when serving as solid electrolytes for lithium-ion batteries. In this paper, Nb-doped LiTi 2 (PO 4) 3 has been synthesized by solid-state reaction method and the structural, vibrational and dielectric studies are systematically investigated. The X-ray diffraction conforms that the Nb-doped LiTi 2 (PO 4) 3 compound has NASICON structure, i.e. rhombohedral with space group R-3c. The average crystallite size and lattice constant are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…More energy loss is observed as more ionic collision occurs. The pattern of dielectric constant and loss in this study is similar to other NASICON-based solid electrolyte works [ 28 , 38 ]. These authors stated that their NASICON-based electrolytes have the behavior of an ionic conductor.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…More energy loss is observed as more ionic collision occurs. The pattern of dielectric constant and loss in this study is similar to other NASICON-based solid electrolyte works [ 28 , 38 ]. These authors stated that their NASICON-based electrolytes have the behavior of an ionic conductor.…”
Section: Resultssupporting
confidence: 87%
“…The highest conductivity achieved is 4.74 × 10 −6 S cm −1 when x = 0.4 ( Table 2 ). Rao et al [ 28 ] stated that the differences in conductivity are typically related to the connectivity between grains, which have a higher concentration of imperfections near the grain boundary. The authors reported a similar trend of conductivity variation where the highest conductivity value is 4.25 × 10 −6 S cm −1 for LiTi 2 (PO 4 ) 3 system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…62 It is observed from the films that the diameter of the arc decreases for the films deposited on Al and Ag substrates, which results in an increase in the electrical conductivity due to the reduction in resistance of the samples. 33 The results are well reflected in our PEC analysis where the film deposited on the Ag substrate shows higher open-circuit voltage and efficiency. The Nyquist plot is well fitted using ZSimpWin 3.21 software.…”
Section: Resultssupporting
confidence: 69%
“…The presence of larger particle size in Ag/AZTSe is then expected to be beneficial to conductivity. 33 As the particle size of the thin films increases, this implies that the amount of grain boundary decreases. The extent of grain boundary scattering decreases because of the decrease in the amount of grain boundary.…”
Section: Resultsmentioning
confidence: 99%